PENGARUH ADAPTASI NEW NORMAL TERHADAP RENDAHNYA MINAT BELAJAR SISWA DI SMAN 2 LAMBU KABUPATEN BIMA - Wahyuningsih, Sri; Darwis, Darwis; Waluyati, Ida (Universitas Tanjungpura, 2022)
Problems related to the adaptation of the new normal to the low learning interest of New Normal students is a new life where people continue to carry out various activities as usual but still apply the health protocols that have been set by the government so that the spread of the Covid 19 Virus can be overcome. In contrast, if people ignore health protocols, the implementation of the new standard will cause the number of Covid-19 cases to increase. The new normal's performance impacts the world of education, where students are currently studying at home by implementing the online learning process. This study aimed to determine the influence and level of adaptation of the new normal to the low interest in student learning at SMAN 2 Lambu, Bima Regency. The research approach used is quantitative. This research is located at SMAN 2 Lambu, Bima Regency. The research variable used is the new normal adaptation as an influence variable (X), while student interest in learning is an affected variable (Y). The research population is 206 students. The sample used was 103 students. The research subjects were students of classes X and XI. The research time is two (2) months, from June to July 2022. Data collection using a questionnaire or questionnaire. The data analysis technique used a simple linear regression formula and the determinant test. The results of this study indicate that based on the analysis of simple linear regression equations with a value of = 1830679 + 2281873 X = 2464940, while the value of Ftable is 3.94, therefore there is an effect of adapting the new normal as the X variable to the low interest in student learning as the Y variable in SMAN 2 Lambu, Bima Regency. The level of influence in the two research variables is 86.5%, while other variables determine 13.5%.